Band anisotropy and effective mass renormalization in strained metallic VO2 (101) thin films - A. D’Elia; V. Polewczyk; A. Y. Petrov; G. Vinai; L. Li; C. W. Zou; S. J. Rezvani; A. Marcelli (NPG Asia Materials)
Abstract We explore how strain impacts the band structure of metallic-phase VO2 thin films deposited on TiO2(101) substrates. Employing a combination of X-ray absorption linear dichroism and valence band measurements, we demonstrate that strain can alter the intrinsic band structure anisotropy of metallic VO2. Our findings reveal that reducing the thickness of VO2 films leads to a more isotropic band structure. This observation is further supported by an analysis of the electronic population redistribution in the $${d}_{{||}}{-}{π }^{* }$$ d || − π * bands, which affects the screening length and induces effective mass renormalization. Overall, our results underscore the potential of strain manipulation in tailoring the electronic structure uniformity of thin films, thereby expanding the scope for engineering VO2 functionalities.